1999
DOI: 10.1007/s000110050425
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophil cationic protein (ECP) as a mediator of inflammation in acute asthma, during resolution and during the monitoring of stable asthmatic patients treated with inhaled steroids according to a dose reduction schedule

Abstract: This study suggests that the resolution of acute asthma exacerbations during treatment could be followed using ECP determinations. In stable asthmatics on inhaled steroids and with normal ECP levels, a dose reduction could be indicated. A longer period after tapering off steroids is proposed to confirm the benefit of ECP measurements for controlling asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Specific IgE serves as a mediator of the allergic response and ECP a marker of allergic inflammation in asthma [28,29]. Our results confirmed that all our asthmatic patients were atopic with an inflammatory response manifesting ≥ 1 sensitization to common inhalant allergens and significantly elevated plasma ECP concentration.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Specific IgE serves as a mediator of the allergic response and ECP a marker of allergic inflammation in asthma [28,29]. Our results confirmed that all our asthmatic patients were atopic with an inflammatory response manifesting ≥ 1 sensitization to common inhalant allergens and significantly elevated plasma ECP concentration.…”
Section: Discussionsupporting
confidence: 80%
“…Animal models and clinical studies in humans have indicated an important role for Th2 cells producing IL-4, IL-5 and IL-13 in the pathogenesis of allergic asthma [1], with the induction of a Th1 response that seems to aggravate an inflammatory process [2]. Specific IgE serves as a mediator of the allergic response and ECP a marker of allergic inflammation in asthma [28,29]. Our results confirmed that all our asthmatic patients were atopic with an inflammatory response manifesting $ 1 sensitization to common inhalant allergens and significantly elevated plasma ECP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…37 IgE acts as a mediator of the allergic response in asthma. 38 Our results confirmed that all asthmatic children have increased IgE levels than their control counterparts. In a previous study, IgE level has been shown to be high in severe and mild asthma (43% and 50% respectively ).…”
Section: Discussionsupporting
confidence: 81%
“…15 Because this risk increases with duration of asthma and age of patients, adequate treatment with anti-inflammatory medications is particularly germane to the elderly asthmatic population. 15 Moreover, although patients reach clinical stability during hospitalization, their airways remain inflamed for several weeks, predisposing them to suffering relapses during this time 16 ; the risk of relapse is as high as 45% by 8 weeks after hospital discharge, 17 which makes it important that these patients have close follow-ups after discharge. However, a recent study 18 indicates that over half of patients with asthma do not have follow-up visits with a primarycare physician after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%